Investor overreactions to transnational peer firm earnings: The role of accounting standards - Herkenhoff, Manuel; Nienhaus, Martin (Contemporary Accounting Research, 2025)
Abstract This study finds that accounting standards play an important role in cross‐border investor reactions to peer firm earnings. Specifically, we document that when international peer firms report under the same accounting standards, investors overreact to peer firms' earnings announcements. Using a sample of 35,116 firm‐pair‐years from 51 countries between 2000 and 2010, we show that heightened information transfers for international same‐standard firms are followed by predictable price reversals when investors observe own‐firm earnings. However, overreactions are not present for international firm‐pairs that follow different accounting standards. While we find that institutional investors learn over time, overreactions do not decline among retail investors. Additional tests suggest that overreactions cause significant excess volatility, which results in economically significant costs. Collectively, our findings document an unintended consequence of financial reporting harmonization in the form of increased investor overreactions.